Enhancing Plasma Density through Periodic Dielectric Grating Structures-Numerical Simulations - Kakulia, D.; Tavzarashvili, K.; Noselidze, I.; Kajaia, G. (Advanced Electromagnetics, 2024)
This paper proposes an idea of the use of Dielectric Resonators (DRs) as concentrators of alternating magnetic fields for plasma density control applications. The study involves numerical simulations using the Method of Auxiliary Sources (MAS) to analyze Dielectric Frequency Selective Surfaces (DFSS) composed of periodic dielectric elements. Materials with variable dielectric permittivities, including E-Glass, Plexiglass, Taconic CER-10, and Teflon are considered, and their resonance properties are investigated. Results indicate that DFSSs can create strong magnetic fields at resonance frequencies, which can be utilized for plasma density regulation in processes like thin film deposition. The results demonstrate that materials with lower dielectric permittivity, such as Plexiglass and Teflon, exhibit higher resonance quality factors, while higher permittivity materials like E-Glass and Taconic CER-10 show poorer quality factors. The study emphasizes the potential of DFSSs in enhancing plasma density and improving industrial applications, highlighting the importance of precise geometric configurations and material properties in designing effective dielectric resonators.